The Effect of Green Brand Positioning, Green Brand Attitude, and Green Brand Knowledge on Green Purchase Intention: A Case Study of Uwinfly Electric Bikes in Sumenep City - Wulandari, Nurlaily; Maromi, Izzul (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of green brand positioning, green brand attitude, and green brand knowledge on green purchase intention on Uwinfly Electric Bicycle in Sumenep City District. Using a quantitative approach, with purposive sampling techniques. Data was collected through a questionnaire distributed to 80 respondents who knew and had a purchase interest in the Uwinfly brand in Sumenep City District. The data analysis method used is multiple linear regression analysis with the help of the Statistical Package for Social Science (SPSS) software. The results showed that the green brand positioning variable did not have a significant influence on green purchase intention. Green brand attitude has a significant positive influence on green purchase intention. Green brand knowledge has a significant positive influence on green purchase intention. Then, simultaneously the variables of green brand positioning, green brand attitude and green brand knowledge have a significant effect on green purchase intention.Keywords: Green Brand Positioning, Green Brand Attitude, Green Brand Knowledge, Green Purchase Intention